Abstract: The purpose of this research is to determine the application of humanistic existential group guidance with meditation techniques to students of XI IPA 5 SMA Negeri Colomadu in the academic year 2021/2022. This research uses a qualitative descri - Ramadhanis, WuriKusuma (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
Abstract: The purpose of this research is to determine the application of humanistic existential group guidance with meditation techniques to students of XI IPA 5 SMA Negeri Colomadu in the academic year 2021/2022. This research uses a qualitative descriptive method with focus group discussion approach (group discussion). Sources of data from this study are students who have the potential to experience feelings of worthlessness, principals, BK teachers. Data collection techniques used are interviews, observation, and documentation. The data validity technique used is technical triangulation and source triangulation. The data analysis technique used is pattern matching, in this study there were 8 (eight) subjects who had the potential to experience feelings of worthlessness. The object of this research is a humanistic existential group guidance service with meditation techniques. To prevent feelings of worthlessness in XI IPA 5 SMA Negeri Colomadu in the academic year 2021/2022. Based on data collection conducted through Focus Group Discussion, there were 8 students who had the potential to experience feelings of worthlessness. Group discussion was conducted 3 (three) times. After the group discussion was conducted, it was found that humanistic existential group guidance with appropriate meditation techniques was applied to prevent feelings of worthlessness. This is indicated by the understanding of students' thinking which has begun to open more widely in responding to the characteristics of feelings of worthlessness. Keywords : Group Guidance, Existential, Humanistic, Meditation, Feeling Worthless, Emotion, Personal, Social